A Understanding career calling: historical roots and practical relevance for school counselors - Alfan, Robbani; Solehuddin, M; Nurihsan, Juntika; Riksa Yustiana, Yusi (Jurnal Konseling dan Pendidikan, 2024)
This article critically examines the origins and evolution of the term "career calling" and its relevance for school counselors. Tracing its roots from Ancient Greece to modern times, the concept of career calling has shifted from a spiritual vocation to a broader, secularized understanding, yet remains deeply tied to prosocial motivation and meaningful work. Employing the Critical Interpretive Synthesis approach, this study systematically and interpretatively analyzes the historical and social evolution of 'career calling.' By integrating comprehensive literature reviews from databases such as JSTOR, PubMed, ERIC, and Google Scholar, the methodology facilitates a nuanced exploration of how the concept has transformed, focusing on its impact on the professional role of school counselors. The evolution of the term "calling" from its traditional religious roots to a more secular interpretation highlights the broadening scope of the concept in modern contexts, reflecting shifts in Western cultural norms and values. This transformation underscores the ongoing debate among scholars about the definition of calling, with some advocating for a return to its historical, prosocial origins and others embracing its contemporary relevance to individual fulfillment and professional identity. The insights gained from this study not only expand school counselors' understanding of the profound implications of career calling, enhancing their perception of professional identity, but also provide a foundational basis for the development of instruments specifically tailored for measuring career calling among school counselors. Furthermore, these insights are instrumental in designing effective career calling development interventions, enabling school counselors to better support students in aligning their educational paths with their life's purposes.